Kinerja Keuangan sebagai Mediator Hubungan Struktural Aset, Sumber Pembiayaan dan Nilai Perusahaan - Herlina Rasjid; Meriyana Franssisca Dungga; Hamka Masse (Jurnal Ilmu Manajemen, 2026)
This study aims to analyze the effect of asset structure and financing sources on firm value with financial performance as a mediating variable in the Indonesian agricultural industry. The sample consisted of 24 agricultural companies during the 2020–2024 period, and the analysis was conducted using Structural Equation Modeling – Partial Least Squares (SEM-PLS). The findings reveal that financial performance, measured by Return on Assets (ROA) and Net Profit Margin (NPM), does not mediate the relationship between asset structure or financing sources and firm value, which was measured using Tobin’s Q and Price to Book Value (PBV). Asset structure, represented by fixed asset proportion and current ratio, does not significantly affect financial performance, as fixed assets in agricultural companies are often less productive in the short term and current ratio does not always reflect efficiency. Similarly, financing sources, measured by debt to assets ratio and debt to equity ratio, show no significant impact on financial performance, as high risk in agriculture makes debt financing increase interest burdens without ensuring profitability. These results highlight that firm value in the agricultural sector is more strongly shaped by external factors. Thus, improving firm value requires integrated strategies combining efficient asset management, innovative financing policies, and adaptation to external dynamics.